OP0191-PC Prevalence of inflammatory back pain in a UK primary care population. (23rd January 2014) - Murphy, D.J.; Kyle, S.; Manhas, R.; Mascarenhas, R.F.; Mackay, K.R.
Abstract : Background: It is accepted that seronegative spondyloarthritides such as Ankylosing Spondylitis (AS) are frequently misdiagnosed or diagnosed late in the disease course; early diagnosis and subsequent treatment improves patient symptoms and reduces the likelihood of permanent functional impairment. The presence of inflammatory back pain (IBP) is a key diagnostic symptom, yet few non-specialist doctors are confident in identifying it 1 . To aid diagnosis well validated criteria exist to guide non-expert clinicians and help flag patients potentially suffering with IBP 2 . Little is known about the true frequency of IBP in the primary care population, with the only study estimating the prevalence at 15% 3 . Prevalence of AS is estimated at 0.2-1.2% 4 . Objectives: To determine the prevalence of inflammatory back pain in a UK General Practice population. Methods: For a six month period in 2011 all patients aged between 18 and 40 years presenting to their General Practitioner for the first time with back pain in two UK medical practices were screened using the ASAS inflammatory back pain criteria. The two practices involved serve a population of 26500 patients. Those answering positively to 4 or more of the questions were defined as suffering IBP and referred to a local rheumatology service for further investigation. Results: During the six month study period 55 patients presented to their GP with their first episode of back pain. All were white Caucasian. Six patients (11%) were defined as suffering inflammatory back pain as per ASAS criteria; 5 were male (83%) and 1 female (17%). 50% of these patients were subsequently diagnosed with a seronegative spondyloarthritis. Conclusions: In our study population the prevalence of inflammatory back pain was 11%; 50% of these patients were diagnosed with Ankylosing Spondylitis. Our study involved a small sample size; further work is required to more confidently estimate the prevalence of inflammatory back pain in patients presenting to their General Practitioner. References: NE Foster. Barriers and progress in the treatment of low back pain. BMC Medicine 2011; 9: 108. Sieper J, Van der Heijde D, Landewe R, Burgos-Vagas R, Collantes-Esteves E. New criteria for inflammatory back pain in patients with chronic back pain. Ann Rheum Dis 2009; 68: 784-788. Underwood MR, Dawes P. Inflammatory Back Pain in Primary Care Rheumatology 1995; 34: 1074-77. Sieper J, Rudwaleit M, Khan MA, Braun J. Concepts and Epidemiology of Spondyloarthropathy Best Practice & Res Clin Rheumatol 2006; 20: 401-417 Disclosure of Interest: None Declared